YIG thick film as substrate overlay for bandwidth enhancement of microstrip patch antenna - Hasan, Intan Helina; Hamidon, Mohd Nizar; Ismail, Alyani; Ismail, Ismayadi; Mekki, Anwer Sabah; Mohd Kusaimi, Muhammad Asnawi; Azhari, Saman; Osman, Rosiah (Institute of Electrical and Electronics Engineers, 2018)
Research on microstrip patch antenna (MPA) has been growing in the past few decades due to its planar profile and easy fabrication. Its simplicity of structure, which includes a conductive patch, a dielectric substrate, a ground plane, and a microstrip feeder, is making it more popular for integration in devices which are more focused on miniaturization and flexibility. There are, however, a few disadvantages of MPA, such as narrow bandwidth, low power, and limited inexpensive material selection if a current printed circuit board etching fabrication technique is used. Ferrite substrates are known to be able to help overcome this issue, but the properties of bulk ferrites are difficult to control. This paper aims to solve this problem by using thick-film technology, which utilizes a screen printing method to include ferrite thick film in the MPA structure as substrate overlay to help enhance the performance of MPA. Yttrium iron garnet was chosen as the starting ferrite nanopowders, and the preparation and characterization of the ferrite thick-film paste were carried out to investigate properties of the thick film. Results showed that the thick film showed moderate permittivity and permeability, which is suitable for MPA fabrication. The actual fabricated MPA with ferrite thick-film inclusion on FR4 substrate showed that the thick film improved the performance of MPA with low firing temperature of 200 °C. For MPA which is designed to work at 5.8 GHz, the return loss and -3-dB bandwidth improved 100% and 73%, respectively. In conclusion, ferrite thick-film inclusion in MPA fabrication has proven to improve the performance of the antenna in terms of return loss and bandwidth enhancement.